Reciprocity towards nature in the biodiversity science–policy interface - Sandra Díaz; Unai Pascual (People and Nature)
Abstract The notion of reciprocity between humans and the rest of the living world is receiving increasing attention in the environmental sciences and science–policy international bodies. Here we first discuss different meanings of reciprocity, then we discuss this notion in relation to the conceptual framework of the Intergovernmental Platform on Biodiversity and Ecosystem Services (IPBES), to date the most prominent international mechanism informing the science–policy interface on living nature. We show that the notion of human–nature reciprocity is recognized and is explicitly included in the IPBES conceptual framework. However, to date, it has received comparatively little attention. To overcome this, we argue that, rather than creating new separate ad‐hoc categories that risk compromising the internal consistency and pluralism of the IPBES conceptual framework, co‐created across different disciplines, worldviews and policy frames, a more fruitful path would be to interpret all its components in a reciprocity light, with stronger emphasis on the human shaping of, and practices of care towards the rest of the living world. Such attention to reciprocity should contribute to the evolution of IPBES and related science–policy initiatives, by incorporating a plurality of perspectives, while still maintaining the framework operational by the continued engagement of multiple disciplines and stakeholders. In terms of policy and action, this would involve more attention to pre‐existing practices of care for nature—of which we provide a few illustrative examples—and new practices inspired by them or created afresh. Read the free Plain Language Summary for this article on the Journal blog.